Faktor Yang Mempengaruhi Volume Sampah Medis dan Sistem Pengelolaannya pada Unit Pelayanan Rawat Inap (Studi di RSD. Dr. H. Koesnadi Bondowoso) - Pujiati, Rahayu Sri; Arthadaya, Asri Swastinugraha (IKESMA, 2007)
A study to determine number of patients, number of nurses and number of practical students on the volume of medical waste as well as management of the waste has been carried out at Dr. H. Koesnadi Provincial Hospital Bondowoso, East Java. Data were collected using questionnaire, interview, observation, and documentation method. From statistical analysis with Multiple Linier Regression it was found out significant effect (a=5%) of independent factors on dependent factor with coefficient of determination R2 0.525 Analysis of partial correlation volume. From the waste management point of view there has been pointed out two handicaps, i.e. applied standard operational procedure (SOP) of the hospital has not yet fully accommodate the national SOP on medical waste management, and there were deviation of the hospital SOP at the daily practice. It is recommended improve the practicing hospital SOP and working out in monitoring at implementation scale. This study also showed at tight coordination with medical record unit is needed to have a better prediction on medical waste produced. Key words : medical waste, medical waste management, hospital, inpatient